Web information systems engineering - WISE 2007 : 8th international conference on web information systems engineering Nancy, France, December 3-7, 2007, proceedings - International Conference on Web Information Systems Engineering (8th : 2007 : Nancy, France); Benatallah, Boualem (Heidelberg, New York : Springer, 2008)
57